Financing Higher Education in Sub-Saharan Africa: A Proposed Model Based on the Experiences of Ugandan Higher Education Institutions and Exemplary Practices from the Asian Tigers - Miiro, Farooq; Ssekamanya, Siraje Abdallah (Springer, 2020)
Financing higher education has become one of the most contentious educational issues in both developed and third world countries. Among the causes highlighted by researchers are changing fiscal policies and government resource allocation priorities, coupled with rapid increases in college-going populations. Today, there is an upsurge in the numbers of colleges and enrollments all over the world. This upsurge and the forces of globalization, which put demands on institutions in terms of international rankings and the need to adopt the latest technologies, are putting enormous fiscal pressure on higher education institutions and their funders. Increasing enrollments without sufficient funding lead to substandard facilities and a decline in academic standards. To close that funding gap, institutions have resorted to privatization, which includes (inter alia) tuition charges and other fees. This has effectively turned the traditional model of higher education upside down. The challenge is: How do universities ensure they admit only the most qualified students and provide them with the best instruction, using state-of-the-art facilities, in a learning system run by highly qualified and motivated faculty staff? Against that background, this chapter analyzes best practices for financing higher education in developing countries that have vibrant higher education sectors (such as Malaysia), together with the challenges, practices, and experiences of funding Ugandan higher education institutions. The chapter ultimately suggests a suitable framework for higher education financing in Uganda and similar sub-Saharan African countries.